Voucher für Glasfaseranschlüsse: Warum Bund und Länder auf sie verzichten sollten - Torsten J. Gerpott (Wirtschaftsdienst, 2020)
Seit einigen Jahren wird von verschiedenen Seiten empfohlen, nachfrageseitig den Ausbau von Glasfaseranschlüssen in Deutschland mit 'Gigabit-Vouchern' staatlich zu subventionieren. Solche Gutscheine weisen jedoch erhebliche Nachteile auf. Bundes- und Landesregierungen sollten sie deshalb nicht einsetzen. – – Gigabit vouchers are a state-paid subsidy, which recompenses households and small and medium enterprises for a portion of the costs they incur through subscribing to Fiber-To-The-Building/-Home (FTTB/H) access offers. Various sources claim that such vouchers are an attractive means to increase demand for and supply of FTTB/H lines in Germany. However, the subsidy is plagued by serious flaws: vouchers are likely to attract only a marginal number of additional customers; to have undesired distributive side effects; to trigger minimal welfare gains; and to generate unnecessary administration costs. Thus, German federal and state governments are well advised to refrain from introducing gigabit vouchers.
Keywords: D62; H20; L96; 330